Pengaruh Servant Leadership, Job Satisfaction, Organizational Identification terhadap Voluntary Turnover Intention dengan Ta'awun sebagai variabel intervening pada karyawan muslim PT Bayyas Bio Fuels - Anggoro, Calvin; Sudarti, Ken; Nurcholis, Lutfi (Faculty of Economics and Business | Universitas Diponegoro, 2024)
This study aims to analyze the influence of Servant Leadership, Job Satisfaction, and Organizational Identification on Voluntary Turnover Intention with Ta’awun as an intervening variable among Muslim employees at PT Bayyas Bio Fuels. The research method used is Structural Equation Modelling (SEM) with the aid of Partial Least Square (PLS) software wich includes tests of convergent validity, discriminant validity, composite reliability second order confirmatory factor analysis, R2, 푄2, and hypothesis testing This study employes primary data obtained through questionnaires distributed to 50 Muslim employees at PT Bayyas Bio Fuels.The results indicated that Servant Leadership and Job Satisfaction negative and significantt affect Organizational Identification and Voluntary Turnover Intention. Additionally, Ta’awun as an intervening variable also negative and significantt affects Voluntary Turnover Intention. Organizational Identification negative and significantt Voluntary Turnover Intention, meaning that higher Organizational Identification leads to negative and significantt Voluntary Turnover Intention among employees. This research provides practical contributins for company management to enhance Servant Leadership, Job Satisfaction, and Organizational Identification as strategies to reduce employees Voluntary Turnover Intention. Implementing the values of Ta’awun in the workplace is also proven effective in increase employee loyality and reducing Turnover Intention.